Transformable multirotor with two-dimensional multilinks: modeling, control, and motion planning for aerial transformation. (2nd July 2016) - Zhao, Moju; Kawasaki, Koji; Okada, Kei; Inaba, Masayuki
Abstract : In this study, we investigated a novel type of the multirotor aerial vehicle with two-dimensional multilinks to demonstrate stable aerial transformation for high mobility in three-dimensional environments. Our goal was to tackle the challenge of traversing narrow spaces or gaps, which is one of the difficulties for existing structure of multirotors, especially in the cluttered indoor environment of disaster sites. The research involved three steps. First, we developed the modeling of the link modules that compose a multirotor with two-dimensional multilinks and conducted a quadrotor prototype. Second, we derived a stable flight control method for aerial transformation on the basis of linear-quadratic-integral optimal control. Third, we investigated the motion planning for the aerial transformation using a state validation method and path optimization in the joint space to maintain the stability during transformation. Successful aerial transformation and the ability of the prototype to negotiate narrow gaps were demonstrated, confirming the feasibility and utility of our proposed transformable multirotor for aerial maneuvering in complex three-dimensional environments. Graphical Abstract: